An introduction to ocean remote sensing - Martin, Seelye (Cambridge University Press, 2014)
"Fully updated, with significant new coverage of advances in satellite oceanography and results from new satellite missions, the second edition of this popular textbook introduces students to how remote sensing works, how to understand observations from Earth-observing systems, and the observations' importance to physical and biological oceanography. It provides full explanations of radiative transfer, ocean surface properties, satellite orbits, instruments and methods, visible remote sensing of biogeochemical properties, infrared and microwave retrieval of sea surface temperature, sea surface salinity retrieval, passive microwave measurements, scatterometer wind retrieval, altimetry and SAR. This new edition now also includes descriptions of the online archives where data can be obtained, and where readers can obtain online tools for working with the data - enabling hands-on engagement with real-world observations. This is an ideal textbook for graduate and advanced undergraduate students taking courses in oceanography, remote sensing and environmental science, and provides a practical resource for researchers and Earth science professionals working with oceanographic satellite data"--